Intra- and Inter-Host Assessment of Bartonella Diversity with Focus on Non-Hematophagous Bats and Associated Ectoparasites from Brazil - Ikeda, Priscila [UNESP]; Marinho Torres, Jaire; Perles, Livia [UNESP]; Lourenco, Elizabete Captivo; Herrera, Heitor Miraglia; Oliveira, Carina Elisei de; Zacarias Machado, Rosangela [UNESP]; Andre, Marcos Rogerio [UNESP] (Mdpi, 2020)
The relationship among bats, ectoparasites and associated microorganisms is important to investigate how humans can become exposed to zoonotic agents. Even though the diversity of Bartonella spp. in bats and ectoparasites has been previously reported, the occurrence of gltA genotypes within hosts has not been assessed so far. We aimed to investigate the genetic diversity of Bartonella spp. in non-hematophagous bats and associated ectoparasites by assessing cloned gltA Bartonella genotypes in intra- and inter-hosts levels, as well as by using three additional molecular markers. Overall, 13.5% (18/133) bat blood samples, 17.18% bat flies (11/64) and 23.8% (5/21) Macronyssidae mite pools showed to be positive for Bartonella spp. Seventeen positive samples were submitted to gltA-cloning and three clones were sequenced for each sample. We also obtained 11, seven and three sequences for nuoG, rpoB and ftsZ genes, respectively. None were positive for the other target genes. We found at least two genotypes among the three gltA-cloned sequences from each sample, and 13 between all the 51 sequences. Among the nuoG, rpoB and ftsZ sequences we found eight, five and three genotypes, respectively. In the phylogenetic analysis, the sequences were positioned mainly in groups related to Bartonella identified in rodents, bats and bat flies. Herein, we showed the genetic diversity of Bartonella in bat's blood and associated ectoparasites samples at both intra- and inter-host levels.
Keywords: genetic diversity; Chiroptera; gltA; Bartonella